Hubungan Faktor-Faktor Predisposisi dengan Kejadian Osteoarthritis pada Ibu Rumah Tangga yang Berobat di Puskesmas Keai Durian - Nanda Novziransyah (PRIMER (Prima Medical Journal), 2020)
Predisposing factors are thought to have a relationship to the incidence of osteoarthritis (OA). Some predisposing factors associated with and increased risk of OA are age, genetics, and body mass index (BMI). The purpose of this study was to determine the relationship of predisposing factors to the incidence of osteoarthritis in housewives who were treated at Puskesmas Kedai Durian for the period February-March 2019. This study used an analytical study with a Cross Sectional approach. This study uses a population of housewives who seek treatment at Puskesmas Kedai Durian. The sample in this study were 72 people taken through accidental sampling techniques. Data was taken using a questionnaire distributed to housewives who went to the Puskesmas Kedai Durian and analyzed by the chi-square test. The data analysis technique used is univariate and bivariate analysis. In the results of the study it was found that there was an association of age with the incidence of osteoarthritis (p=0,000); the relationship between genetics and the incidence of osteoarthritis (p = 0,000); the relationship between body mass index (BMI) and the incidence of osteoarthritis (p=0.020). So it can be concluded that there is a relationship between predisposing factors with the occurrence of osteoarthritis in housewives who seek treatment at Puskesmas Kedai Durian in February-March 2019. Keywords: Body Mass Index (BMI), Osteoarthritis (OA), Predisposing Factors, Age, Genetics.